Making LGUs gender-responsive a primer for local chief executives. - Philippines. National Commission on the Role of Filipino Women (Manila National Commission on the Role of Filipino Women, 2002)
This book is intended for new local chief executives(LCE) of Local Government units. According to the author, its aim is "to make clear the importance of being sensitive to gender in determining the needs and resources of the locality, in planning and carrying out programs and in running the government machinery itself." This book shows the role of local chief executives in achieving gender responsiveness of local government units and shows where they can get assistance.
Published with support from the Canadian International Development Agency.
Keywords: Women in development -- Philippines; Local government -- Philippines; Local officials and employees -- Philippines -- Handbooks, manuals, etc